2003
DOI: 10.1044/1058-0360(2003/089)
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth

Abstract: Telehealth offers the potential to meet the needs of underserved populations in remote regions. The purpose of this study was a proof-of-concept to determine whether voice therapy can be delivered effectively remotely. Treatment outcomes were evaluated for a vocal rehabilitation protocol delivered under 2 conditions: with the patient and clinician interacting within the same room (conventional group) and with the patient and clinician in separate rooms, interacting in real time via a hard-wired video camera an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(41 citation statements)
references
References 4 publications
2
35
0
4
Order By: Relevance
“…Research has demonstrated that synchronous telepractice methods produce similar clinical outcomes when compared with in-person speech-language pathology services for neurogenic communication disorders, fluency disorders, voice disorders, dysphagia, and childhood speech and language disorders (Hill & Theodoros, 2002; Lowe, O’Brian, & Onslow, 2013; Mashima & Brown, 2011; Mashima & Doarn, 2008; Swanepoel & Hall, 2011; Theodoros, 2008). In addition to positive clinical outcomes that mirror those of in-person services, client and clinician satisfaction have been remarkably positive across the majority of studies (Brennan, 2006; Brennan, Georgeadis, & Baron, 2002; Georgeadis, Brennan, Barker, & Baron, 2004; Kully, 2002; Mashima et al, 2003), a finding consistent with other areas of telehealth research (Cardoso & Steinberg, 2010). …”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…Research has demonstrated that synchronous telepractice methods produce similar clinical outcomes when compared with in-person speech-language pathology services for neurogenic communication disorders, fluency disorders, voice disorders, dysphagia, and childhood speech and language disorders (Hill & Theodoros, 2002; Lowe, O’Brian, & Onslow, 2013; Mashima & Brown, 2011; Mashima & Doarn, 2008; Swanepoel & Hall, 2011; Theodoros, 2008). In addition to positive clinical outcomes that mirror those of in-person services, client and clinician satisfaction have been remarkably positive across the majority of studies (Brennan, 2006; Brennan, Georgeadis, & Baron, 2002; Georgeadis, Brennan, Barker, & Baron, 2004; Kully, 2002; Mashima et al, 2003), a finding consistent with other areas of telehealth research (Cardoso & Steinberg, 2010). …”
Section: Introductionsupporting
confidence: 58%
“…Three additional treatment studies for voice disorders are found in the literature that are not tied to patients with PD (Fu, Theodoros, & Ward, 2015; Mashima et al, 2003; Rangarathnam et al, 2015). Fu et al (2015) delivered intensive voice therapy (i.e., eight sessions over three weeks) via videoconferencing to 10 women with vocal nodules and found significant improvements in acoustic, perceptual, quality-of-life measures, and nodule size at post-treatment, mirroring the outcomes in a separate in-person study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, telerehabilitation has been shown to be effective in the treatment of speech and language disorders, including voice disorders (Constantinescu et al, 2010; Mashima et al, 2003; Theodoros et al, 2006; Tindall, Huebner, Stemple, & Kleinert, 2008), apraxia of speech (Lasker, Stierwalt, Spence, & Calvin-Root, 2010), and stuttering (Kully, 2000; O’Brian, Packman, & Onslow, 2008; Wilson, Onslow, & Lincoln, 2004). Telerehabilitation has also been utilized to train the production of personally relevant speech in participants with Broca’s aphasia (Goldberg, Haley, & Jacks, 2012).…”
mentioning
confidence: 99%
“…The third possibility is a combination of the above two paths: starting with a gradual reduction of frequency, followed by a follow-up program and a boost IVT when needed. Telepractice might be a useful tool in follow-up (Fu, Theodoros, & Ward, 2015b;Mashima et al, 2003;Rangarathnam et al, 2015). Further research is needed to confirm whether these innovative service delivery models should be the new standard for voice therapy.…”
Section: Auditory-perceptual Evaluation Groupmentioning
confidence: 99%